The Meaning of Immediate Phrase in Article 44 Section (1) UUJN JO. UUJN-P IN The Signing of The Minuta of Notary Deed - Agung Iriantoro (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
The purpose of this study is to determine the meaning of the expression instantly in Article 44 Paragraph (1) UUJN jo. UUJN-P while signing Notary minuta deed. This study will discuss the meaning of words immediately after the deed is read, the deed is signed by each appeared, witness, and notary as stipulated in Article 44 Paragraph (1) UUJN jo. UUJN-P in the implementation of the Notary position, as well as the validity of the Notary deed minuta that were not signed by the Notary in conjunction with the appearers and witnesses. This study determined when the appearers, witnesses, and notaries should sign the draft minuta deed, in order to determine the minuta’ legitimacy. This research employs a normative legal method. The findings of this study indicate that the legal norms set forth in Article 44 Paragraph (1) UUJN jo. UUJN-P should be implemented in accordance with and consistent with the legal norms set forth in Article 16 Paragraph (1) letter m UUJN-P, specifically the word immediately in Article 44 Paragraph (1) UUJN jo. UUJN-P must be read and interpreted to mean that it will be signed immediately following the Nota’s reading of the deed. If the draft Minuta of Notary Deed are not prepared in accordance with the legal norms referred to in Article 16 Paragraph (1) letter m UUJN-P, the Minuta Deed will have deficiencies (gebreken), which will serve as the basis for their invalidity (niet-rechtsgeldig).